Burning mouth syndrome in Iraqi patients: a preliminary study of 38 cases (Mustansiria Dental Journal, 2018)
The complain of burning sensation in the mouth can be said to be a symptom of other disease or a syndrome in its own right of unknown etiology. In patients where no underlying dental or medical causes are identified and no oral signs are found, the term burning mouth syndrome should be used.To obtain base line information on the prevalence of the oral problems and clinical features co-existing with burning mouth syndrome patients.The study group consisted of 38 (11 males and 27 females) burning mouth patients, they were examined to evaluate the oral health status.Of 38 patients, who verbalized their complaints, 63.1% complained of subjective oral dryness, 26.3% had taste disturbances; the most prevalent site with burning sensations was the tongue 65.7%.Burning mouth syndrome patients in our environment are principally women, other symptoms include dryness and altered taste is common in those patients.